Sea quark Sivers distribution - Hui Dong; Du-xin Zheng; Jian Zhou (Physics Letters B, 2019)
We compute sea quark Sivers distribution within color glass condensate (CGC) framework. It has been found that up to the leading logarithm accuracy, the collinear twist-3 approach and the CGC calculation yield the same result for sea quark Sivers distribution in the dilute limit. We further verify that transverse momentum dependent factorization is consistent with CGC treatment at small x for the case of transverse single spin asymmetry in open charm quark production in semi-inclusive deeply inelastic scattering process in an overlap kinematical region.